Working with QGIS - Menke, Kurt; Smith, Richard, Jr.; Pirelli, Luigi; Safari eBooks ([Place of publication not identified] : Packt, 2017)
"QGIS is a user-friendly open source Geographic Information System (GIS) that runs on Linux, Unix, MacOS X, and Windows. The popularity of open source Geographic Information Systems and QGIS in particular has been growing rapidly over the last few years. This video is a practical, hands-on course updated for QGIS 2.14 and provides you with clear, step-by-step exercises to help you apply your GIS knowledge to QGIS. Through clear, practical exercises, this video will quickly and painlessly introduce you to working with QGIS. This video takes you from installing and configuring QGIS to handling spatial data to creating great maps. You will learn how to load and visualize existing spatial data and create data from scratch. You will learn about important plugins, perform common geo-processing and spatial analysis tasks, and automate them with processing. We will cover how to achieve great cartographic output and print maps. Finally, you will learn how to extend QGIS using Python and even create your own plugin."--Resource description page.
Title from title screen (viewed September 26, 2017).
Date of publication from resource description page.
Keywords: Geographic information systems -- Computer programs; Geodatabases -- Computer programs; Cartography -- Computer programs; Geospatial data -- Data processing; Electronic books